Do People With Severe Traumatic Brain Injury Benefit From Making Errors? A Randomized Controlled Trial of Error-Based and Errorless Learning. (December 2017) - Ownsworth, Tamara; Fleming, Jennifer; Tate, Robyn; Beadle, Elizabeth; Griffin, Janelle; Kendall, Melissa; Schmidt, Julia; Lane-Brown, Amanda; Chevignard, Mathilde; Shum, David H. K.
Background. Errorless learning (ELL) and error-based learning (EBL) are commonly used approaches to rehabilitation for people with traumatic brain injury (TBI). However, it is unknown whether making errors is beneficial in the learning process to promote skills generalization after severe TBI. Objective. To compare the efficacy of ELL and EBL for improving skills generalization, self-awareness, behavioral competency, and psychosocial functioning after severe TBI. Method. A total of 54 adults (79% male; mean age = 38.0 years, SD = 13.4) with severe TBI were randomly allocated to ELL or EBL and received 8 × 1.5-hour therapy sessions that involved meal preparation and other goal-directed activities. The primary outcome was total errors on the Cooking Task (near-transfer). Secondary outcome measures included the Zoo Map Test (far-transfer), Awareness Questionnaire, Patient Competency Rating Scale, Sydney Psychosocial Reintegration Scale, and Care and Needs Scale. Results. Controlling for baseline performance and years of education, participants in the EBL group made significantly fewer errors at postintervention (mean = 36.25; 95% CI = 32.5-40.0) than ELL participants (mean = 42.57; 95% CI = 38.8-46.3). EBL participants also demonstrated greater self-awareness and behavioral competency at postintervention than ELL participants ( P < .05). There were no significant differences on other secondary outcomes ( P > .05), or at the 6-month follow-up assessment. Conclusion. EBL was found to be more effective than ELL for enhancing skills generalization on a task related to training and improving self-awareness and behavioral competency.